Low-pressure twin-fluid atomization: Effect of mixing process on spray formation - Zaremba, Matouš; Weiß, Lukas; Malý, Milan; Wensing, Michael; Jedelský, Jan; Jícha, Miroslav (International journal of multiphase flow, 2017)
The present work comparably examines four different twin-fluid atomizers operated under the same operating conditions. Spray formation was examined by several approaches. The internal flow pattern was estimated using a simplified analytical approach, and the results were supported by the observation of the liquid discharge in the near-nozzle region. A high-speed back illumination was used for visualisation of the primary breakup. In the region of fully developed spray, the dynamics of droplets was studied using a phase-Doppler analyser (PDA). The information obtained from all methods was then correlated. Results show that the spray formation process depends mainly on the internal design of twin-fluid atomizer at low gas to liquid ratios (GLR). The amount of gas influences the character of the internal two-phase flow, a mechanism of the liquid breakup, droplet dynamics and a resulting drop size distribution. Differences among the atomizers are reduced with the increase in GLR. Moreover, it was shown that a certain mixing process can inherently create the annular internal flow which generates a stable spray characterized by relatively low mean droplet size.